Preparation and mechanic properties of multi-wall carbon nanotube reinforced alumina matrix composites by spray drying and hot-pressing sintering. (18th June 2021) - Tan, Songlin; Zhuang, Yongqi; Yi, Jianhong
Abstract: The multi-wall carbon nanotube (MWCNT) reinforced alumina (Al2 O3 ) matrix composites were fabricated by spray drying and vacuum hot-pressing sintering. The mechanical properties of the composites with different mass fractions of MWCNT were studied. The flexural strength and fracture toughness of the composite were 498.3 MPa and 5.69 MPa·m 1/2, respectively, which were about 55.3% and 84.7% higher than that of pure Al2 O3 . With the increase in the content of MWCNT, the Vickers hardness and relative density of the composite decreased gradually. The correlation between the microstructure and the mechanical properties of the composite was analyzed.